Prompting And Positive Reinforcement Implementation To Improve Eye Contact With 5 – 6 Years Old Autism Spectrum Disorder Student - Christina Makmeser Iriani Kbarek; Septiyani Endang Yunitasari; Meilania I Prihatiningsih; Deborawati Hasugian; Yuni Christina; Yuliance Peday (International Conferences on Early Childhood Education Proceedings, 2023)
The problem in this study is the lack of eye contact in children with Autism Spectrum Disorder. This study aims to see and describe the improvement of eye contact in children with Autism Spectrum Disorder by applying prompting and positive reinforcement. The method of research is to use a qualitative approach with descriptive methods. Data collection in this study used observation, interview, and documentation techniques. The results showed that AL students experienced an increase in eye contact, where before prompting, the response from the child ranged from 0-5 seconds. After starting the AL, the child's response increased between 10-60 seconds, depending on the prompting done. Another improvement found in AL children is that they can respond to stimuli given by the teacher.